Cyclone vulnerability assessment of the central coast of Bangladesh: A comprehensive study utilizing FAHP and geospatial techniques - Md Abdullah Salman; Mahmudul Hasan Rakib; Shacin Chandra Saha; Md Emdadul Haque; Md Sabbir Hossen (PLoS ONE, 2025)
The coastal areas of Bangladesh are recognized as a major South Asian center for cyclone landfall. This research develops a comprehensive tropical cyclone mapping strategy utilizing the Fuzzy Analytical Hierarchy Process (FAHP) and geospatial techniques to analyze the vulnerability distribution in the central coastal regions of Bangladesh. Eighteen spatial features, categorized into physical, social, and mitigation capacity criteria, were assessed to evaluate vulnerability. The output indicates that the southern peripheral districts- Bhola, Borgona, and Patuakhali are more vulnerable to tropical cyclones due to factors such as historical cyclone tracks, proximity to the coastline, low elevation, gentle slopes, high population density (including vulnerable groups such as females, the disabled, and agricultural workers), poor socioeconomic status, and land covers (crops and vegetations) prone to damage. Mitigation measures in these areas, including cyclone warnings, embankments, and access to shelters and road networks, are found to be inadequate. Validation through ROC and AUC confirms the accuracy of vulnerability maps. These findings offer critical insights for policymakers, local NGOs, and local administrators to enhance cyclone preparedness and develop targeted mitigation strategies to reduce vulnerability in coastal Bangladesh.